Preparation of cuttlefish ink-porphyrin nanoconjugates and its application in photodynamic-photothermal synergistic treatment of tumor cells - Wang, Wei; Zhang, Yuting; Li, Yan; Huang, Yuzi; Xiao, Shuzhang; Huang, Wenquan; Geng, Peng (Nano and Medical Materials, 2024)
Biologically derived nanomaterials have gained increasing attention in tumor diagnosis and treatment due to their inherent biocompatibility. In this study, a nanoconjugate of cuttlefish ink (M, extracted from cuttlefish ink sacs) and meso-tetra (4-carboxyphenyl) porphyrin (TCPP), termed M-TCPP, was synthesized. The nanoparticle size of M-TCPP was approximately 120 nm, and it could be activated by a 660 nm light to induce the generation of reactive oxygen species (ROS) via TCPP for photodynamic therapy (PDT) of tumor cells. Additionally, when triggered by an 808 nm light (near-infrared light), the cuttlefish ink component efficiently converted light into heat for photothermal therapy (PTT) of tumor cells. Compared to standalone PDT or PTT, the synergistic combination of PDT-PTT resulted in significantly enhanced tumor cell destruction. Moreover, in vitro experiments demonstrated that M-TCPP exhibited no noticeable toxic side effects. The research offers some inspiration for the development of natural multifunctional biomaterials and their use in tumor therapy.